VALUE-BASED EVALUATION OF CULTURAL SIGNIFICANCE IN HISTORIC CHINATOWN AREAS - Rochana, Intan Pramesti; Indrianingrum, Lulut; Rahadini, Ari (International Journal on Livable Space, 2025)
Urban cultural heritage sites face growing challenged from rapid development and limited resources. Local governments must develop strategic plans to improve how they manage and protect these cultural assets. A practical solution is to rank different areas within heritage sites based on their cultural importance, allowing authorities to focus limited resources to which they matter most. Aims: This study demonstrates how to use a systematic evaluation method to determine conservation priorities in Semarang’s Chinatown, a nationally recognized cultural heritage site in Indonesia. Methodology and results: The research used a two-step approach: (1) The initial phase entails spatial mapping of physical characteristics that contribute to cultural significance, and (2) The subsequent phase employs the Analytic Hierarchy Process (AHP) to systematically assess and rank the attributes that characterize the cultural significance of the area. Conclusion, significance, and impact study: The AHP analysis identified three key priority factors: (1) architectural styles predominantly influenced by Chinese cultural influences, (2) the existence and spatial organization of Chinese temples within the urban landscape, and (3) land use patterns that are congruent with the historical character. These important characteristics were identified most concentrated in the Gang Warung corridor and around the Tay Kak Sie and Hoo Hok Bio temples. The findings highlight the necessity of integrating cultural value assessments into preliminary phases of heritage planning. By identifying the most culturally significant area, the study establishes a framework for devising targeted, recourse-efficient conservation strategies applicable to analogous historic urban areas.